How Coffee Capsules Affect the Volatilome in Espresso Coffee - Giuseppe Greco; Estefanía Núñez-Carmona; Marco Abbatangelo; Patrizia Fava; Veronica Sberveglieri (Separations, 2021)
Coffee capsules have become one of the most used methods to have a coffee in the last few years. In this work, coffee was prepared using a professional espresso coffee machine. We investigated the volatilome of four different polypropylene coffee capsule typologies (Biologico, Dolce, Deciso, Guatemala) with and without capsules in order to reveal the possible differences in the VOCs spectra. The volatilome of each one was singularly studied through an analysis by gas chromatography and mass spectrometry (GC–MS), checking the abundance of different VOCs in coffee extracted with and without a capsule protection and compared to its related sample. Furthermore, ANOVA and Tukey tests were applied to statistically identify and individuate the possible differences. As a result, it was found that coffee capsules, offer advantages of protecting coffee from oxidation or rancidity and, consequently extended shelf life as well as did not cause a reduction of volatile compounds intensity. Therefore, it is possible to conclude that the aroma of polypropylene coffee capsule extraction is not damaged compared to a traditional espresso.